(untitled) (Bangladesh Journal of Botany, 2018)
Effect of GA3 and pruning on flowering and yield in Assam lemon (Citrus limon Burm. F.) were studied. Ten treatments were imposed for two seasons (summer and winter) in which significant among the treatments were found for profuse flowering and its yield. Among the different treatments, the pooled data of two seasons showed that G1P1 (GA3 50 ppm single spray plus 15 cm shoot pruning) recorded the highest flower per branch (29.75.), fruitlets per branch (6.4) and yield (10.45 t/ha) as compared to the control plants 26.5 flowers per branch, 5.8 fruitlets per branch and 9.43 mt/ha, respectively. Therefore, combination of GA3 50 ppm single spray + 15 cm shoot pruning is most promising which can be recommended for improvement of yield in lemon cv. Assam lemon.